On-site energy generation in the manufacturing industry: effects on the variability of the net electricity demand - Meskell, Craig (My University, 2020)
Local distribution system operators (DSOs) are currently dealing with the unpredictability and high variability of energy production coming from an increasing number of distributed variable renewable energy (VRE) systems. On the demand side, DSOs could count on the predictable electricity demand profile that characterises the manufacturing industry and effectively represents a baseload for the grid. The necessity to decrease the environmental impact of the industry sector is driving manufacturing facilities towards on-site renewable energy generation, affecting the predictability of the net demand profile. An on-site VRE system has been simulated for an existing manufacturing plant in Ireland to investigate the effects of on-site energy generation on the variability of the net demand. It is shown that on-site VRE generation increases not only the amplitude but also the occurrence of rapid fluctuations in the net demand during the year. The integration of a flexible technology such as a gas turbine for combined heat and power presents only limited benefits. Adding battery storage to the on-site system does improve the variability of the on-site integrated system but a high variability is still present. The manufacturing facility remains a net consumer in all the analysed cases.
PUBLISHED
Keywords: Distribution system operators (DSOs); Variable renewable energy (VRE) systems; Electricity; Smart & Sustainable Planet; ENERGY EFFICIENCY